Population in the Twelfth Census - Cummings, John (Journal of Political Economy, 1903)
FOR the student of economics the chief interest attaching to Vols. I and II of the twelfth census -the volumes on population-lies in the statistical estimate which he looks to find therein of the economic character, or value, or activity of the inhabitants of the country considered as productive power. HIe is interested in the mass and application of this prime economic force; that is to sav, in the extent and growth of population, on the one hand, and, on the other, in the distribution of its members into industrial groups, as engaged in agriculture, manufactures, trade, commerce, or in some sort of manual, mechanical, or professional labor. He is interested in the direction of what Mayo-Smith has called the " labor-force" of the country " in cultivating the ground, in extracting minerals from the soil, in turning raw material into forms fitted to satisfy lhuman wants, in transporting commodities from one place to another, in distributing products among the different members of the community, or in rendering personal services." Otlher statistical information about population than that which regards its natural movement and industrial occupation may have great economic significance, as, for example, its geographical distribution, mnigrations and concentration in great urban centers, its